Investigação pré-clínica para desfibriladores externos - Vieira, Amanda Assunção (2013)
There is consensus that the physical characterizations of medical devices defibrillation, especially those obtained by mechanical testing and electrical safety tests, are a critical step in transforming innovative concepts into reliable products for use in humans. However, considering that the chest ventricular defibrillation applied by an electric shock is not necessarily an innocuous procedure, since studies have shown as much damage as morphological functional impairment of the heart caused by successive shocks, the information obtained by testing pre -clinical tests allow to relate the safety and efficacy of electric shock in experimental animals to determine any undesirable side effects in normal use and assess whether they are at risk due to the intended device´s performance.Investigations into the cardioversion efficacy in response to induced ventricular fibrillation and macroscopic changes and biochemical changes that occur in porcine hearts were performed after capacitive discharge truncated exponential shock applied defibrillator produced nationally and another reference "golden standard" international market leader . . It was concluded that the defibrillator prototype when applied with energy 100J demonstrated better efficacy in terminating ventricular fibrillation and had less injury than the defibrillator reference with the same energy, making it suitable for the insertion of the national and international market. This study will help to raise the standard of technology and increase the supply of qualified health equipment produced in Brazil, replacing and / or decreasing imports and providing a secure next generation equipment